Innate Resistance to Leishmania amazonensis Infection in Rat Is Dependent on NOS2 - Chen, Yun-Fu; Yu, Si-Fei; Wu, Chang-You; Wu, Na; Shen, Jia; Shen, Juan; Gao, Jiang-Mei; Wen, Yan-Zi; Hide, Geoff; Lai, De-Hua; Lun, Zhao-Rong (Frontiers in Microbiology, 2021)
Leishmania infection causes diverse clinical manifestations in humans. The disease outcome is complicated by the combination of many host and parasite factors. Inbred mouse strains vary in resistance to Leishmania major but are highly susceptible to Leishmania amazonensis infection. However, rats are highly resistant to L. amazonensis infection due to unknown mechanisms. We use the inducible nitric oxide synthase (Nos2) gene knockout rat model (Nos2−/− rat) to investigate the role of NOS2 against leishmania infection in rats. Our results demonstrated that diversion toward the NOS2 pathway is the key factor explaining the resistance of rats against L. amazonensis infection. Rats deficient in NOS2 are susceptible to L. amazonensis infection even though their immune response to infection is still strong. Moreover, adoptive transfer of NOS2 competent macrophages into Nos2−/− rats significantly reduced disease development and parasite load. Thus, we conclude that the distinct L-arginine metabolism, observed in rat macrophages, is the basis of the strong innate resistance to Leishmania. These data highlight that macrophages from different hosts possess distinctive properties and produce different outcomes in innate immunity to Leishmania infections.